2020
DOI: 10.1093/jas/skaa003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of added copper, alone or in combination with chlortetracycline, on growth performance and antimicrobial resistance of fecal enterococci of weaned piglets

Abstract: Studies suggest a link between added copper (Cu) and co-selection of antimicrobial resistance (AMR) in Enterococcus spp., but data are inconsistent. This study aimed to assess the impact of added Cu, alone or with a feed-grade antimicrobial, on growth performance, transferable Cu resistance gene (tcrB) prevalence, abundance of tcrB in fecal community DNA, and AMR in fecal enterococci in weaned piglets. A total of 320 barrows (DNA 200 × 400, DNA Genetics) weaned at approximately 21 d of age with 7.4 kg (7.4 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…Our results are consistent with the study of Wang et al (2019) who investigated that administration with 75 mg/kg CTC did not affect average daily gain and feed efficiency in weaned piglets. However, a high concentration of CTC, such as 400 and 440 mg/kg CTC, could improve average daily gain, feed intake, and body weight in weaned piglets (Capps et al, 2020; Williams et al, 2018). Thus, we speculated that these different effects of CTC might be partially due to the dosage of CTC.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the study of Wang et al (2019) who investigated that administration with 75 mg/kg CTC did not affect average daily gain and feed efficiency in weaned piglets. However, a high concentration of CTC, such as 400 and 440 mg/kg CTC, could improve average daily gain, feed intake, and body weight in weaned piglets (Capps et al, 2020; Williams et al, 2018). Thus, we speculated that these different effects of CTC might be partially due to the dosage of CTC.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility toward copper (Cu), zinc (Zn), cadmium (Cd), and mercury (Hg) was tested, as previously described (Sharifi et al, 2015 ; Capps et al, 2020 ). Briefly, overnight cultures were spotted onto Mueller–Hinton agar (Oxoid) supplemented with different concentrations (0.05 to 40 mM) of ZnCl 2 (Carlo Erba), HgCl 2 (Sigma Aldrich), and CdSO 4 (Sigma Aldrich) resuspended in distilled water, and CuSO4 (Merck Millipore) adjusted to pH 7.2 with 1 M NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Although copper can prevent bacterial growth, some bacterial species can tolerate high levels of copper by acquiring copper-resistance genes via horizontal gene transfer ( Davison, 1999 ). However, the link between antimicrobial resistance development and increased copper supplementation has been inconsistent, as other studies reported that copper did not increase copper-resistant bacteria in pigs ( Agga et al., 2014 ; Capps et al., 2020 ).…”
Section: Coppermentioning
confidence: 98%